Coaching Penerapan Teknik Asertif terhadap Kecemasan Pada Warga Binaan di LPKA Kelas II Jakarta - Aprilyani, Ratnasartika; Kartasasmita, Anna Mariani; Ratnawati, Sri; Widya Puteri, Ika Apriati (Universitas Negeri Gorontalo, 2025)
Prisons have many problems, raising curiosity to explore further the ways of inmates in adapting and socializing. Inmates who are in prisons tend to be able to experience psychological pressure where they are separated from their families, have difficulty taking control of themselves, lose their models, which makes these psychological problems arise. The inmates hope to be accepted by the community. The problem of Lapas Kelas II prison partners is the lack of educators who have the competence to provide education and training to inmates whose prison sentences are almost complete in order to reduce their anxiety when they re-enter the community. The coaching results showed that the behavior change and the improvement of the participants' communication asertive behavior varied greatly. This can be seen in succession of the highest to low scores related to the level of communication skills. Andikpas experienced the most significant behavioral changes in treatment using coaching techniques.